2020
DOI: 10.25225/jvb.20056
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the trophic niches of the golden jackal Canis aureus across the Eurasian continent associated with biogeographic and anthropogenic factors

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
0
13
0
1
Order By: Relevance
“…Alternatively, the observed spatial and habitat partitioning may also be related to the partial diet overlap; in other words, the two species may use different areas for foraging. The golden jackal and the red fox are both generalist carnivores consuming a wide range of prey species across the Eurasian continent, from small mammals to wild ungulates; moreover, both species can alternatively behave as scavengers or active predators, even considering larger prey species [ 13 , 85 87 ]. Our research showed that in Friuli–Venezia Giulia region the golden jackal and the red fox mainly shared three important prey categories, which were wild ungulates, small mammals, and medium-sized mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the observed spatial and habitat partitioning may also be related to the partial diet overlap; in other words, the two species may use different areas for foraging. The golden jackal and the red fox are both generalist carnivores consuming a wide range of prey species across the Eurasian continent, from small mammals to wild ungulates; moreover, both species can alternatively behave as scavengers or active predators, even considering larger prey species [ 13 , 85 87 ]. Our research showed that in Friuli–Venezia Giulia region the golden jackal and the red fox mainly shared three important prey categories, which were wild ungulates, small mammals, and medium-sized mammals.…”
Section: Discussionmentioning
confidence: 99%
“…We used Normalized Difference Vegetation Index (NDVI) as environmental variables that can potentially affect feeding ecology of foxes (Doherty et al, 2015; Tsunoda & Saito, 2020). We extracted NDVI data (0.1‐degree resolution) from the National Aeronautics and Space Administration website (https://neo.sci.gsfc.nasa.gov/view.php?datasetId=MOD_NDVI_M).…”
Section: Methodsmentioning
confidence: 99%
“…We extracted NDVI data (0.1‐degree resolution) from the National Aeronautics and Space Administration website (https://neo.sci.gsfc.nasa.gov/view.php?datasetId=MOD_NDVI_M). We used monthly values of NDVI for 2001 to calculate an annual mean value (Tsunoda & Saito, 2020; Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations